Electrospun poly(ε-caprolactone)/poly(glycerol sebacate) aligned fibers fabricated with benign solvents for tendon tissue engineering - Iorio, Francesco; El Khatib, Mohammad; Wöltinger, Natalie; Turriani, Maura; Di Giacinto, Oriana; Mauro, Annunziata; Russo, Valentina; Barboni, Barbara; Boccaccini, Aldo R. (Journal of Biomedical Materials Research Part A, 2024)
The electrospinning technique is a commonly employed approach to fabricate fibers intended for various tissue engineering applications. The aim of this study is to develop a novel strategy for tendon repair through the use of aligned poly(ε-caprolactone) (PCL) and poly(glycerol sebacate) (PGS) fibers fabricated in benign solvents, and further explore the potential application of PGS in tendon tissue engineering (TTE). The fibers were characterized for their morphological and physicochemical properties; amniotic epithelial stem cells (AECs) were used to assess the fibers teno-inductive and immunomodulatory potential due to their ability to teno-differentiate undergoing first a stepwise epithelial to mesenchymal transition, and due to their documented therapeutic role in tendon regeneration. The addition of PGS to PCL improved the spinnability of the polymer solution, as well as the uniformity and directionality of the so-obtained fibers. The mechanical properties were in the range of most TTE applications, specifically in the case of PCL/PGS 4:1 and 2:1 ratios. Compared to PCL alone, the same ratios also allowed a better AECs infiltration and growth over 7 days of culture, and triggered the activation of tendon-related genes (SCX, COL1, TNMD) and the expression of tenomodulin (TNMD) at the protein level. Concerning the immunomodulatory properties, both PCL and PCL/PGS fibers negatively affected the immunomodulatory profile of AECs, up-regulating both anti-inflammatory (IL-10) and pro-inflammatory (IL-12) cytokines over 7 days of culture. Overall, PCL/PGS 2:1 fibers fabricated with benign solvents proved to be the most suitable composition for TTE application based on their topographical cues, mechanical properties, biocompatibility, and teno-inductive properties.
CRIS-Team Scopus Importer:2024-09-27
Keywords: amniotic epithelial stem cells; electrospinning; poly(glycerol sebacate); poly(ε-caprolactone); scaffolds; tendon tissue engineering

Impact of morphological features and chemical composition of tendon biomimetic scaffolds on immune recognition via Toll-like receptors - Gil-Cantero, Sara; Iorio, Francesco; Ünalan, Irem; Kurtuldu, Fatih; Künig, Sarojinidevi; Wenhardt, Claus; Pinnaro′, Veronica; Aigner-Radakovics, Katharina; Steinberger, Peter; Boccaccini, Aldo R.; Stöckl, Johannes (Biomaterials Science, 2024)
Tendinopathies are a major worldwide clinical problem. The development of tendon biomimetic scaffolds is considered a promising, therapeutic approach. However, to be clinically effective, scaffolds should avoid immunological recognition. It has been well described that scaffolds composed of aligned fibers lead to a better tenocyte differentiation, vitality, proliferation and motility. However, little has been studied regarding the impact of fiber spatial distribution on the recognition by immune cells. Additionally, it has been suggested that higher hydrophilicity would reduce their immune recognition. Herein, polycaprolactone (PCL)-hyaluronic acid (HA)-based electrospun scaffolds were generated with different fiber diameters (in the nano- and micro-scales) and orientations as well as different grades of wettability and the impact of these properties on immunological recognition has been assessed, by means of Toll-like receptor (TLR) reporter cells. Our results showed that TLR 2/1 and TLR 2/6 were not triggered by the scaffolds. In addition, the TLR 4 signalling pathway seems to be triggered to a greater extent by higher PCL and HA concentrations, but the alignment of the fibers prevents the triggering of this receptor. Taken together, TLR reporter cells were shown to be a useful and effective tool to study the potential of scaffolds to induce immune responses and the results obtained can be used to inform the design of fibrous scaffolds for tendon repair.
CRIS-Team Scopus Importer:2024-08-23

Processing and characterization of aligned electrospun gelatin/polycaprolactone nanofiber mats incorporating borate glass (13-93B3) microparticles - Ege, Duygu; Pourshahrestani, Sara; Iorio, Francesco; Reinfelder, Heike; de Ligny, Dominique; Boccaccini, Aldo R. (Biomedical Materials (Bristol), 2023)
Aligned biodegradable fibers incorporating bioactive glass particles are being highly investigated for tissue engineering applications. In this study, 5, 7 and 10 wt% melt-derived 1393B3 borate glass (BG) microparticles (average size: 3.15 µm) were incorporated in 83 wt% polycaprolactone (PCL) and 17 wt% gelatin (GEL) (83PCL/17GEL) solutions to produce aligned electrospun composite nanofiber mats. Addition of 5 wt% BG particles significantly increased the alignment of the nanofibers. However, further incorporation of BG particles led to reduced degree of alignment, likely due to an increase of viscosity. Mechanical tests indicated a tensile modulus and tensile strength of approximately 51 MPa and 3.4 MPa, respectively, for 5 wt% addition of 1393B3 BG microparticles, values considered suitable for soft tissue engineering applications. However, with the increasing amount of 1393B3 BG, the nanofiber mats became brittle. Contact angle was reduced after the addition of 5 wt% of 1393B3 BG particles from∼45° to∼39°. Cell culture studies with normal human dermal fibroblast (NHDF) cells indicated that 5 wt% 1393B3 BG incorporated nanofiber mats were cytocompatible whereas higher doping with 1393B3 BGs reduced biocompatibility. Overall, 5 wt% 1393B3 BG doped PCL/GEL nanofiber mats were aligned with high biocompatibility exhibiting desirable mechanical properties for soft tissue engineering, which indicates their potential for applications requiring aligned nanofibers, such as peripheral neural regeneration.
CRIS-Team Scopus Importer:2023-09-08
Keywords: bioactive glasses; borate glasses; electrospinning; nanofiber; peripheral nerve tissue regeneration; soft tissue engineering